Decreased risk of nosocomial transmission of hepatitis B and C viruses among hemodialysis patients in Southern Bulgaria - Radka T Komitova; Elitsa N Golkocheva-Markova; Ani K Kevorkyan; Lubomira Nikolaeva-Glomb; Vanya R Rangelova; Tanya I Kostadinova; Tsvetelina Chardakova; Mariya V Atanasova; Tencho D Tenev; George S Kiprin; Simon K Sariyan; Ralitsa D Raycheva; et al. (Journal of Infection in Developing Countries)
Introduction: Hepatitis B (HBV) and (HCV) virus infections represent a nosocomial risk in hemodialysis (HD) patients. We aimed to evaluate the risk among adult HD patients in southern Bulgaria.